UPAYA REHABILITASI LAHAN KRITIS DENGAN PENERAPAN TEKNOLOGI AGROFORESTRY SISTEM SILVOPASTORAL DI DESA OEBOLA KECAMATAN FATULEU KABUPATEN KUPANG - Matatula, Jeriels (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2009)
Abstract The increase is a critical area of unity between the simultaneous condition biofisik, social, economic and culture associated with the land as The main factors of production, and implementation of policies that consider less sustainable. Fatuleu sub-district is one of the district with 29,800 inhabitants The population, which consists of 11 villages and 1 village. Livelihood of communities is 41.41% is agricultural and animal husbandry. The goal of this activity are: 1). Rest and empowering potential of silvopastoral agroforestry system as a source of economic income people; 2). Changing the views and attitudes of farmers on land that has not been applying the concept of silvopastoral system; 3). Changing the system of land use monoculture (traditional) into Multicultural (modern). Bring or change the pattern of land use monokuler need to be multikuler process. The method is implemented with a participatory approach to counseling about technology silvopastoral agroforestry system for the rehabilitation of critical land. Demplot making model with the condition that the land biofisik Social Economy and society, development demplot plants with the implementation of silvicultural techniques that include tree species selection, soil management techniques, planting techniques and maintenance. This activity is held on the land of farmers and the main commodities planted on land that is provided is deplot forestry plants namely Mahoni with planting distance of 6 x 6 meters with the planting holes 30x30x30 cm, while the terrace plants and Lamtoro turi. Implementation of activities or physical realization in location, the form of: 1) Preparation of land for planting and seedling; 2) Making terrace; 3) Pengalian hole; 4) Planting. Planting activities have been done in the area who have plot, but given the climate conditions of heat and rain have not been evenly down the steps that are taken with give irrigation teets. Key words: rehabilitation, angroforestry, and silvopastoral